The Human Understanding of Garments: An Exploratory Study on Technology Inspired Clothing Design for Young Adults with Anxiety - Brinkley, Tamara; Bynum, Kaylee; Filinger, Claudia (Kansas State University. K-State Libraries, 2022)
The purpose of this exploratory study investigates the clothing preferences and choices of people who have anxiety issues. The goal of this project is three-fold: 1) studying the relationship between people's anxiety and their clothing choices; 2) experiment with different apparel technologies to accommodate the wants and needs of people who have anxiety issues, and 3) developing an apparel collection that incorporates apparel technologies to address the anxiety issues of the wearer. The basis for this project revolves around innovative apparel technology, anxiety issues, and their relationships with clothing preferences and choices. The research study included questions about the effect of color, comfort, and fit in clothing in correspondence to participants' anxiety as well as their demographics. Our project “HUG” is focused on the subjects within our 18–25-year target market.
Kirmser Undergraduate Research Award - Group category, grand prize
Keywords: Clothing Preferences; Apparel Technology; Project HUG (Human Understanding of Garments); Optitex; Compression Vest; Anxiety